Navigating ortho care amidst war crisis: insights from Al-Aqsa Martyrs’ Hospital’s orthopedic department at Gaza Strip - Abdulwhhab Abu Alamrain; Abdulwhhab Abu Alamrain; Mohammed Halimy; Mohammed Halimy; Hitham Toman; Hitham Toman; Alaa Kassab; Alaa Kassab; Majdi Alkhaldi; Majdi Alkhaldi; Yosef Alderdasawe; Yosef Alderdasawe; et al. (Frontiers in Public Health, 2025)
The war in Gaza has triggered an unprecedented humanitarian crisis and severely impacted the healthcare system. It has overwhelmed orthopedic care at Al-Aqsa Martyrs’ Hospital, the only public hospital serving the middle region of the Gaza Strip. With over a million displaced individuals and a sharp rise in war-related injuries, the department has been operating under extreme constraints, including shortages of medical supplies, staff, and infrastructure. The orthopedic department, initially small and under-equipped, has rapidly expanded and adapted to handle mass casualties. This has involved restructuring staff shifts, implementing a three-team 24-h rotation system, and repurposing existing facilities to accommodate the influx of patients. Emergency care evolved around a fluidic triage system, and surgical capacity was extremely strained. The repurposed obstetrics and gynecology theaters and delivery rooms became primary operating rooms, with two-thirds of all surgeries being orthopedic-related. Innovative solutions, such as field hospitals and tents for dressing, have helped alleviate some of the pressure. The introduction of the Dressing Under General Anesthesia (DUGA) system has improved wound care for severe injuries. International collaboration, particularly with Médecins Sans Frontières (MSF) and other NGOs, has played a critical role in supplementing medical services and expertise, providing medical and surgical supplies, and facilitating certain procedures. Despite these adaptations, the department remains overwhelmed. Resource limitations have caused delays in essential procedures, leading to complications such as non-union fractures and infections. Additionally, coordination between local and international teams has been challenging, underscoring the need for a more structured response to improve efficiency. The study highlights the adaptation and resilience of the orthopedic department at Al-Aqsa Martyrs’ Hospital. It underscores the urgent need for policy reforms to enhance emergency preparedness, expand surgical capacity, and develop a sustainable, resilient healthcare system. Key recommendations include standardizing clinical protocols, strengthening supply chains, and supporting overburdened and burnout medical staff. Addressing these challenges is crucial to sustaining orthopedic care in Gaza’s war-torn healthcare system.